“Sistema de control interno para el almacén créditos Madril ubicado en el cantón la Maná provincia de Cotopaxi” - Florencia Suntasig, Tatiana Elizabeth (2020)
The present investigation was carried out with the purpose to design an internal control system for the appliance store “Créditos Madril” as a fundamental part for the good development of its activities, through policies and procedures achieving an adequate management in the process of its operations, which will provide a better service and accurate information to its customers, suppliers and third parties, allowing to maximize profits and minimize risks. This appliance store does not have a well-structured internal control system, which does not allow it to meet the stated goals and objectives and can cause economic losses, efficiency and reasonableness of the accounting information and result in a takeover of wrong decisions. In order to carry out this work, it is necessary to apply an exploratory methodological strategy in which techniques such as the interview with the manager will be used, this will facilitate the detection of the problems existing in the store, in addition the technique of the interview to the employees was applied to be able to use the administrative tool called SWOT analysis, which will identify strengths related to the quality of product or service offered by the company, as well as weaknesses related to the lack of training related to the issue of internal control, lack of a manual of functions and procedures. The contributions that this project will have are to improve the development of operational processes through policies and procedures established in the store. This research project was important because, through an internal control system, the appliance store will be able to obtain an adequate control of all operations that are carried out daily, obtaining reliability in administrative and economic information, fully complying with the policies applied. The impact that this project had was social and economic because it achieved the satisfaction of the clients obtaining profits in the sales, the beneficiaries of this project are the owner and the staff that work in the store, helping to develop the environment where they work daily.